Le roman saoudien contemporain face à ses défis - Salwa Almaiman (Arabian Humanities)
Ever since its emergence in the history of Saudi literature, the novel has been considered a troublesome type. A loose category made up of odd bits and ends, barely worthy of being referred to as “adab” (literature), the novel provoked little interest, contrary to the superior genre represented by poetry, “the Diwān (register) of the Arabs”. Since the early 1990s, this state of things has changed considerably and all observers of the Arab literary scene wonder at these novels which come out every year and that get the attention of the press, critics, and other social actors unrelated to the literary world. The fact that new titles keep coming out despite the difficulties linked to publishing and to the novel’s diffusion networks raises many issues regarding both the legitimacy of the writer and that of the genre itself. Writing a novel remains thus conditional upon meeting several challenges, only too obvious to the writer without recognition.